Economical housing provision in China (1998–2002) – a case study of Beijing - Meng, Fan‐yu; Wong, Francis; Hui, Eddie Chi Man; Feng, Chang-Chun (International Journal of Strategic Property Management, 2010)
Economical housing in China is targeted at the housing needs of middle and lower‐middle income urban households. Subsidies and other preferential policies for the provision of such housing are extended by the government. Economical housing is viewed by the Chinese central government as a fundamental component of the new housing system, which was set up in 1998 following the end of the old public housing system. It has also been used as the main driver for economic growth by the Chinese central government in the past five years. In each of those years, billions of RMB from the national budget has been invested in building economical housing, with the aim of eliminating the large gap between housing prices in the open market and public affordability, as well as to support economic growth. The issue of economical housing in China is intimately tied up with political and social issues. This paper presents a thorough study of the evolution of economical housing from 1998 to 2002 in China. Beijing is chosen as a case study because it is the capital city and has one of the most important real estate markets in the country. Recommendations are also given on the future development of economical housing. First Published online: 18 Oct 2010